Retinoic acid delays initial photoreceptor differentiation and results in a highly structured mature retinal organoid - Carla Sanjurjo-Soriano; Nejla Erkilic; Krishna Damodar; Hassan Boukhaddaoui; Michalitsa Diakatou; Marcela Garita-Hernandez; Daria Mamaeva; Gregor Dubois; Zhour Jazouli; Carla Jimenez-Medina; Olivier Goureau; Isabelle Meunier; et al. (Stem Cell Research & Therapy, 2022)
Abstract Background Human-induced pluripotent stem cell-derived retinal organoids are a valuable tool for disease modelling and therapeutic development. Many efforts have been made over the last decade to optimise protocols for the generation of organoids that correctly mimic the human retina. Most protocols use common media supplements; however, protocol-dependent variability impacts data interpretation. To date, the lack of a systematic comparison of a given protocol with or without supplements makes it difficult to determine how they influence the differentiation process and morphology of the retinal organoids. Methods A 2D-3D differentiation method was used to generate retinal organoids, which were cultured with or without the most commonly used media supplements, notably retinoic acid. Gene expression was assayed using qPCR analysis, protein expression using immunofluorescence studies, ultrastructure using electron microscopy and 3D morphology using confocal and biphoton microscopy of whole organoids. Results Retinoic acid delayed the initial stages of differentiation by modulating photoreceptor gene expression. At later stages, the presence of retinoic acid led to the generation of mature retinal organoids with a well-structured stratified photoreceptor layer containing a predominant rod population. By contrast, the absence of retinoic acid led to cone-rich organoids with a less organised and non-stratified photoreceptor layer. Conclusions This study proves the importance of supplemented media for culturing retinal organoids. More importantly, we demonstrate for the first time that the role of retinoic acid goes beyond inducing a rod cell fate to enhancing the organisation of the photoreceptor layer of the mature organoid.